Hansen's Disease And Tuberculosis : A Case Where Two Granulomatous Illnesses Intersect - Ng, CS; Ban, AYL; Soo, CI; Aziz, AM; Faisal, AH; Ummi, ND; Hassan, T; Roslina, AM (Wiley-Blackwell, 2024)
Indexed by WOS